Granulovacuolar Degeneration in Brains of Senile Cynomolgus Monkeys - Darusman, Huda S.; Agungpriyono, Dewi Ratih; Kusumaputri, Vinka A.; Sajuthi, Dondin; Schapiro, Steven J.; Hau, Jann (Frontiers in Aging Neuroscience, 2019)
Neurons with histopathological changes consistent with granulovacuolar degeneration (GVD) were found in brain sections from aged cynomolgus monkeys (Macaca fascicularis) with clinical and pathological signs of cognitive aging. To our knowledge, this is the first reported description of GVD in non-human primates. GVD-like lesions were found also in age-matched cognitively healthy subjects, albeit in lower numbers, suggesting that they may relate to aging and the increase may have tendency to increase with the memory deficits. The increased incidence of GVD-like lesions in memory-impaired subjects with pahological backgrounds of senile plaques (SPs) and tauopathy is, however, an interesting observation of relevance to the characterization of pathologies in the spontaneous cynomolgus monkey model of human Alzheimer’s type of brain pathology.